Willingness to pay for accessibility under the conditions of residential segregation - Kryvobokov, Marko; Bouzouina, Louafi (International Journal of Strategic Property Management, 2014)
The hypothesis that different income groups have different willingness to pay for accessibility to the city centre is based on the standard monocentric model. This hypothesis is empirically tested with accessibility attributes in a hedonic model of apartment prices in the suburbs of the city of Lyon, France. The conditions of residential segregation are described, and apartment prices in the poor and the rich suburbs are analysed with regression techniques. Travel times to two urban centres are accounted for, as well as centrality and accessibility integral indexes. We found that in the selected areas the hypothesis is true. Spatial differences between the estimates for accessibility measures are significant. In more socially problematic areas, the willingness to pay for better accessibility is higher.First Publish Online: 20 Jun 2014